Air transport and operations: Proceedings of the second International Air Transport and Operations Symposium 2011 - Curran, Richard (IOS, 2013)
This book presents the proceedings of the Second International Air Transport and Operations Symposium, ATOS 2011, held at Delft University of Technology in the Netherlands. The focus of ATOS 2011 and this proceedings is on how air transport can evolve in order to continue to add value in the 21st Century, given its incredible impact in the 20th Century. The book covers a whole range of topics: Aircraft Design and Future Concepts; Air Transport Economics; Air Transport, Environment and Safety; Aircraft Lifecycle Value Engineering; Personal Air Transport System (PATS); Airports and Air Traffic Management (ATM). In this collection of articles the reader will find plenty of stimulating research and challenging ideas to help achieve these goals as we venture into the 2nd century of aviation.